The Influence of Small Micro Industries on Economic Growth - rohadin, rohadin; Yanah, Yanah (Universitas Negeri Semarang, 2019)
The purpose of this study to determine whether SMEs have a role to economic growth and how big the role of SMEs to economic growth in Indonesia. Types of data used are time series data i.e SMEs data and Economic growth data from year 2003 until 2018 in Indonesia.Tool of analyze data used in this research is multiple linear regression. The result of analysis shows that the influence between of SMEs on economic growth in Indonesia is only 12,5%, it means that Small Micro Entreprises do not have a significant influence on economic growth in Indonesia, government to accelerate the development of SMEs in Indonesia in order to contribute to economic growth as in the economic crisis that occurred in 1998 SMEs are able to survive when many large companies are bankrupt. This may be caused by SMEs owners and workers in SMEs do not pay taxes to the government so that not much contribute to the economic growth of the Indonesia. In order for SMEs to contribute to economic growth, must export their products to other countries and support from the government is needed to facilitate SMEs in obtaining capital access from financial institutions.